On group sequential tests based on robust location and scale estimators in the two-sample problem - Andreas Christmann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
The behaviour of group sequential tests in the two-sample problem is investigated if one replaces the classical non-robust estimators in the t-test statistic by modern robust estimators of location and scale. Hampel's 3-part redescending M-estimator 25A used in the Princeton study and the robust scale estimators length of the shortest half proposed by Rousseeuw & Leroy and Q proposed by Rousseeuw & Croux are considered. Of special interest are level, power and the average sample size number of the tests. It is investigated, whether commerical software can be used to apply these tests.
Keywords: 519; Average sample size number; Group sequential test; Length of the shortest half; Outliers; Redescending M-estimator; Robustness; Scale estimator Q